2020
DOI: 10.29067/muvu.626834
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Accounting Manipulation With Beneish Model: A Research on Bist Chemistry, Petroleum, Plastic Index Companies

Abstract: İşletmenin finansal durumunu ortaya koyan bilgiler, muhasebe sürecine dayalı olarak oluşturulan finansal tablolardan elde edilmektedir. Dolayısıyla, finansal tabloların doğruluğu işletmenin tüm paydaşları açısından oldukça önem taşımaktadır. Ancak, muhasebe manipülasyonu yapılması neticesinde finansal tablolarda yer alan bilgiler doğruluğunu yitirmekte ve ilgilileri yanlış yönlendirmektedir. Bu nedenle, muhasebe manipülasyonunun belirlenmesi veya ölçülmesi oldukça önemli bir konudur. Bu çalışmada, Beneish TR m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…Kara, et al (2015) researched 132 BIST firms operating in the Manufacturing Industry in the period of 2010-2012, and 66 firms were classified as manipulators. Güner and Kurnaz (2020), using the financial statement data of 24 companies listed in the BIST chemical, petroleum and plastic sector, found that 3 of them may be doing accounting manipulation, 6 of them have significant evidence of accounting manipulation and 8 of them have very significant evidence of accounting manipulation. Toplu et al (2021), based on the analysis of 104 BIST companies, concluded that 94% of the companies manipulate financial information.…”
Section: The Results Of Empirical Studies Using Beneish Modelmentioning
confidence: 99%
“…Kara, et al (2015) researched 132 BIST firms operating in the Manufacturing Industry in the period of 2010-2012, and 66 firms were classified as manipulators. Güner and Kurnaz (2020), using the financial statement data of 24 companies listed in the BIST chemical, petroleum and plastic sector, found that 3 of them may be doing accounting manipulation, 6 of them have significant evidence of accounting manipulation and 8 of them have very significant evidence of accounting manipulation. Toplu et al (2021), based on the analysis of 104 BIST companies, concluded that 94% of the companies manipulate financial information.…”
Section: The Results Of Empirical Studies Using Beneish Modelmentioning
confidence: 99%